Pentamidine: A Non-Peptide GPIIb/IIIa Antagonist – In Vitro Studies on Platelets from Humans and Other Species - Cox, Dermot; Motoyama, Yukio; Seki, Jiro; Aoki, Toshiaki; Dohi, Miwako; Yoshida, Keizo (Thrombosis and Haemostasis, 1992)
In this paper we show that the non-peptide anti-parasite agent pentamidine is a broad spectrum anti-platelet agent with an IC50 of 1.1 µM in ADP-induced platelet aggregation in human platelet rich plasma (PRP). It had similar activity when collagen, arachidonic acid, platelet activating factor, thrombin and epinephrine were used. It had no effect on platelet intracellular cAMP levels. It inhibited 125I-fibrinogen, 125I-fibronectin and 125I-von Willebrand factor binding to ADP-activated fixed platelets with IC50 values of 160, 160 and 60 nM respectively. Pentamidine showed a high degree of species selectivity with slightly less activity in monkey and dog PRP and little activity in guinea pig, rabbit, rat and mouse PRP compared with human. This was similar to the other RGD analogues tested. This species specificity was shown to be dependent on the species of platelets and independent of the species of fibrinogen. Thus, pentamidine is a potent non-peptide inhibitor of fibrinogen binding to GPIIb/IIIa.